Β-Elemene enhances erlotinib sensitivity through induction of ferroptosis by upregulating lncRNA H19 in EGFR-mutant non-small cell lung cancer. (May 2023) - Xu, Cong; Jiang, Ze-Bo; Shao, Le; Zhao, Zi-Ming; Fan, Xing-Xing; Sui, Xinbing; Yu, Li-Li; Wang, Xuan-Run; Zhang, Ruo-Nan; Wang, Wen-Jun; Xie, Ya-Jia; Zhang, Yi-Zhong; et al.
Abstract: Nearly half of all Asian non-small cell lung cancer (NSCLC) patients harbour epidermal growth factor receptor (EGFR) mutations, and first-generation EGFR tyrosine kinase inhibitors (TKIs) are one of the first-line treatments that have improved the outcomes of these patients. Unfortunately, 20% of these patients can not benefit from the treatment. The basis of this primary resistance is poorly understood. Therefore, overcoming EGFR-TKI primary resistance and maintaining the efficacy of TKIs has become a key issue. β-Elemene, a sesquiterpene compound extracted from Curcuma aromatica Salisb. (wenyujing), has shown potent antitumor effects. In this research, we found that β-elemene combined with erlotinib enhanced the cytotoxicity of erlotinib to primary EGFR-TKI-resistant NSCLC cells with EGFR mutations and that ferroptosis was involved in the antitumor effect of the combination treatment. We found that lncRNA H19 was significantly downregulated in primary EGFR-TKI-resistant NSCLC cell lines and was upregulated by the combination treatment. Overexpression or knockdown of H19 conferred sensitivity or resistance to erlotinib, respectively, in both in vitro and in vivo studies. The high level of H19 enhanced the cytotoxicity of erlotinib by inducing ferroptosis. In conclusion, our data showed that β-elemene combined with erlotinib could enhance sensitivity to EGFR-TKIs through induction of ferroptosis via H19 in primary EGFR-TKI-resistant lung cancer, providing a promising strategy to overcome EGFR-TKI resistance in NSCLC patients. Graphical Abstract: The proposed mechanism of the combinative treatment of erlotinib and β-elemene in NSCLC cells. β-elemene combined with erlotinib could promote ferroptosis and the effect was partly dependent on lncRNA H19. ga1